Attenuated positive psychotic symptoms and the experience of anhedonia. Issue 6 (9th June 2017) - Cooper, Shanna; Kring, Ann M.; Ellman, Lauren M.
Abstract : Background: Deficits in anticipatory pleasure have been consistently shown among chronic, first‐episode, and clinical high risk for psychosis populations, but much less attention has been given to non‐clinical individuals experiencing attenuated positive psychotic symptoms (APPS). Methods: Young adults (N = 1839) were administered the Temporal Experience of Pleasure Scale, which measures anticipatory and consummatory pleasure, and the Prodromal Questionnaire, which measures APPS. Analyses examined (1) total APPS endorsed and (2) comparisons of groups experiencing APPS that were endorsed as distressing (distressing APPS = D‐APPS; experiencing more D‐APPS = high‐D‐APPS, a potentially more clinically meaningful group; experiencing fewer D‐APPS = low‐D‐APPS). Results: Results indicated that anticipatory, but not consummatory, pleasure deficits were associated with elevated APPS. Additionally, the high‐D‐APPS group exhibited significantly less anticipatory pleasure compared with the low‐D‐APPS group, but did not differ in consummatory pleasure. Conclusion: Our results mirror findings in schizophrenia samples and suggest that anticipatory pleasure deficits occur along the entire continuum of psychotic experiences.